Lifetime prediction of copper pillar bumps based on fatigue crack propagation - Zhou, Yuege; Liu, Qingsheng; Ma, Tengfei; Li, Shupeng; Zhang, Xinyu (Frontiers in Materials, 2024)
2.5D package realizes the interconnection of multiple dies through Si interposers, which can greatly improve the data transmission rate between dies. However, its multi-layer structure and high package density also place higher reliability requirements on the interconnection structure. As a key structure for interconnection, copper pillar bump(CPB) has small size, high heat generation, and thermal mismatch with silicon chips. The thermal fatigue failure of CPB has gradually become the main failure mode in 2.5D package. Due to the small size of CPB and the large proportion of intermetallic compound (IMC) layers, the lifetime prediction method of spherical solder joints is no longer suitable for CPB. Therefore, it is necessary to establish a fatigue lifetime prediction method for CPB. This paper establishes a method for obtaining the lifetime of CPB based on the basic theory of fatigue crack propagation. Using the extended finite element simulation method, the crack propagation lifetime of CPB under thermal cycling was obtained, and the influence of different IMC layer thickness on the fatigue lifetime of CPB was analyzed. The results indicated that the fatigue lifetime of cracks propagating in the IMC layer is lower than that of cracks propagating in the solder layer, and an increase in the thickness of the IMC layer leads to a significant decrease in the fatigue lifetime of CPB. The lifetime prediction method for CPB proposed in this paper can be used for reliability evaluation of 2.5D package, and has certain reference value for the study of the lifetime of CPB.